IMPORTANCE OF LEARNING URBAN PLANNING TERMS IN LINGUISTICS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Terminology is primary part of every language vocabulary. Terminology is constantly evolving and creating new terms. Each language has multiple systems of terms within its vocabulary. Describing the distinction between term and word can be challenging, as opinions may vary on their precise definitions. Nonetheless, Here given some definitions for terms and terminology and their formation in Uzbek language to clarify the key features of these two concepts.Definitions for urban planning terms also given in this article